2004
DOI: 10.1002/adem.200400060
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Thermal Stability of Alkylsilane Based Coatings for Membrane Emulsification

Abstract: Conclusions:The experimentally determined values of the power indices x and c describing dependence of conductivity r~f v and permittivity e~f ±c on AC frequency f in polyisoprene-carbon nanocomposite in the vicinity of percolation threshold are consistent with the general scaling principle of the percolation theory v + c = 1. The obtained values of v and c are in agreement with the mechanism of inter-cluster polarisation.The experimentally observed deviation from the relation e~|M-M C | ±s of the statistical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The contact angle of all three membranes strongly increases from nearly zero for the silica-modified membranes to around 129-145°, exceeding the value of θ ) 115°found for hydrophobic smooth FOTS surfaces. 34 The difference is very likely due to surface roughness of the silica membranes that enlarges the contact angle for a hydrophobic material (often referred to as the Lotus effect 35 ). Indeed, for EVAL 44-T-FOTS, the contact angle is about 120°, much lower than for EVAL 27-T-FOTS or PES-T-FOTS (see Table 2).…”
Section: Silylated Silica Membranesmentioning
confidence: 99%
“…The contact angle of all three membranes strongly increases from nearly zero for the silica-modified membranes to around 129-145°, exceeding the value of θ ) 115°found for hydrophobic smooth FOTS surfaces. 34 The difference is very likely due to surface roughness of the silica membranes that enlarges the contact angle for a hydrophobic material (often referred to as the Lotus effect 35 ). Indeed, for EVAL 44-T-FOTS, the contact angle is about 120°, much lower than for EVAL 27-T-FOTS or PES-T-FOTS (see Table 2).…”
Section: Silylated Silica Membranesmentioning
confidence: 99%
“…A possible way to achieve surface hydrophobicity is the deposition of self-assembled monolayers of alkyltrichlorosilanes. These kinds of monomolecular coatings are hydrophobic and they show a good thermal and chemical stability [18].…”
Section: Introductionmentioning
confidence: 99%
“…, microporous glass). Van Rijn et al demonstrated the use of isoporous membranes for emulsification in 2004 . They employed silicon nitride membranes with extremely precise pore size ranging from 1 to 10 μm for this purpose.…”
Section: Vocabularymentioning
confidence: 99%
“…Van Rijn et al demonstrated the use of isoporous membranes for emulsification in 2004. 27 They employed silicon nitride membranes with extremely precise pore size ranging from 1 to 10 μm for this purpose. Molecular sieving: Separation of biomolecules using porous gel structures either by gel filtration or by gel electrophoresis has been used widely in various biological processes.…”
mentioning
confidence: 99%